P357 THE MANAGEMENT OF CHOLESTEROL LEVEL CONTROL WITH LIPID–LOWERING DRUGS IN ITALIAN CLINICAL PRACTICE: FINDINGS FROM THE STREAM (SUPPORTING WITH THE REAL–WORLD EVIDENCE THE ASSESSMENT OF MEDICINES AND HEALTH TECHNOLOGIES) STUDY. (18th May 2022) - Degli Esposti, L; Borghi, C; Galvani, M; Giacomini, E; Manotti, P; Marra, A; Passaro, A; Perrone, V; Pieraccini, F; Sangiorgi, D; Navazio, A
Abstract: The study aimed to evaluate the proportion of patients not reaching their low–density lipoprotein (LDL)–cholesterol target according to their risk profile in real–world settings of Italian clinical practice. This observational analysis was based on administrative and laboratory databases from a pool of Italian Entities covering around 10% of Italian population. All patients included had at least one laboratory LDL test between 2012 and 2019. Presence of lipid–lowering drugs was analyzed in the 6 months before index date (last LDL test detected), during which time adherence to these therapies was measured as proportion of days covered (PDC). Risk profile was assessed based on ESC guidelines.1 Among patients with LDL tests that received lipid–lowering drugs, 49.7% were deemed as very high–risk (VHR), 38.3% at high risk (HR), 12% with other risks (OR). Overall, 80% of patients did not reach their LDL–cholesterol target: 87.2% in the HR–cohort, 82.9% in the VHR–cohort (LDL level target 70 mg/dl and 55 mg/dl, respectively) and 49.6% in OR–cohort (LDL level target 116 mg/dl). Statin and ezetimibe combination was observed only in 6.5% of HR and OR and 10.3% of VHR patients, while patients were mainly in monotherapy with statins (87.5 VHR, 91.2% HR, 90.6% OR). Furthermore, patients adherent to treatment (PDC≥80%) accounted for the 52% of VHR–cohort, 47.2% of HR–cohort and 39.1% of OR–cohort. Our findings highlight the need to optimize the management of cholesterol control, especially among patients at risk. Despite the high proportion of patients not reaching LDL target, sub–optimal levels of adherence and a low use of combination regimens were observed, thus suggesting LDL–control could be supported by increasing adherence and/or the use of combination therapies and, if the target is not yet achieved, by the utilization of more recent therapies. European Heart Journal (2020) 41, 111–188